Consequences of the pandemic constraints on the supply chain of companies: an exploratory approach - Lopes, João M. (2022)
The disruption in the supply chain imposed by the COVID-19 pandemic has posed important challenges for companies. This study explores the consequences of the pandemic on the supply chain of companies, identifying the main problems and proposing solutions for future disruptive situations. The qualitative study presented is based on the study of multiple cases obtained through interviews with Portuguese companies. Exploring the multiple cases of companies revealed that companies with less resilient and more vulnerable supply chains, both upstream and downstream, were most affected by the pandemic. The supply chain that includes redundancies and adopting appropriate risk management tools by companies guarantees greater flexibility for supply chains to adapt more quickly to disruptive situations. This exploratory study contributes to the approach of the Complex Adaptive System theory and brings new insights into the consequences of the pandemic on supply chains.